Proses Penyusunan APB Desa Pemerintah Desa Tanjung Datuk Kecamatan Siak Kecil - Aras Perma; Suharyono Suharyono (Politeknik Negeri Bengkalis, 2020)
The purpose of this study was drafting APBDes Of procesing, the role of community and officials village and constraints in the process of making APBDes. The type date research using case study in qualitative method. This research is find (1) Preparation of the APBDes in Tanjung Datuk Village has been applied accordance with Permendagri No.20 year 2018 matter than Village Financial Management and Permendagri No.114 year 2014 matter than village financial management (2) The contribution of village government official and the society was still lacked in the view of the lacked of participant from Tanjung Datuk village society in various field of activities in the village. Especially, in the development sector. (3) abstacles in the process of darfting in APBDes namely, the delay in transfer of village fund allocation (ADD).